2011
DOI: 10.1590/s1807-59322011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oil from Kelussia odoratissima Mozaff. and the evaluation of its sedative and anxiolytic effects in mice

Abstract: OBJECTIVE:The present study aimed to evaluate the sedative and anxiolytic effects of the essential oils and hydroalcoholic extract of Kelussia odoratissima Mozaff. (K. odoratissima) in mice by utilizing an elevated plus maze. The chemical composition of its essential oil was also determined.METHODS:The hydroalcoholic extract or essential oil fraction from this plant were administered intraperitoneally to male mice at various doses 30 min before testing. The anxiolytic and sedative effects were determined by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…Results of other study (Aklaghi 2008) indicated the flower, stem, and leaves of F. angulata (collected from east-north, Iran) yielded 0.66, 0.54 and 0.43% (w/w), respectively. In agreement with previously published reports, Rabbani et al (2011) reported that the aerial parts of K. odoratissima yielded a 0.4% (v/w). The results of a study (Sonboli et al 2006) indicated the EO yield of the aerial parts (leaves and stem) of T. lasiopetalum (synonym: H. lasiopetalum) collected from west Iran was 0.03% (w/w) based on the dry weight of plant.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Results of other study (Aklaghi 2008) indicated the flower, stem, and leaves of F. angulata (collected from east-north, Iran) yielded 0.66, 0.54 and 0.43% (w/w), respectively. In agreement with previously published reports, Rabbani et al (2011) reported that the aerial parts of K. odoratissima yielded a 0.4% (v/w). The results of a study (Sonboli et al 2006) indicated the EO yield of the aerial parts (leaves and stem) of T. lasiopetalum (synonym: H. lasiopetalum) collected from west Iran was 0.03% (w/w) based on the dry weight of plant.…”
Section: Resultssupporting
confidence: 93%
“…Aklaghi (2008) reported that α-phellandrene and α-pinene are main compositions in flowers, stems, and leaves of F. angulata. In total, 38 compounds in the EO from K. odoratissima were identified; the major compounds were α-pinene (20.1%), 1,8-cineole (18.2%), and Z-ligustilide (15.5%), while the results of other reports indicated that the main components of the EO of K. odoratissima were 3-n butyl phtalide and Z-ligustilide (Rabbani et al 2011;Ghasemi Pirbalouti et al 2012;Sajjadi et al 2013). Various factors, including ecotype, harvesting stage, drying, and extraction methods caused on this variation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Volatile constituents of K. odoratissima were reported by the authors in advance. The main constituents of the volatile oil are phthalides with z-ligustilide as the major constituent (11). However, to the best of authors knowledge, this paper was the first report on nonvolatile components of K. odoratissima.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, it is traditionally used as a medicinal plant to treat hypertension, inflammation, ulcers and cardiovascular diseases (53). There is limited literature on the pharmacological properties of this plant, yet recent studies have shown that the hydro-alcoholic extract of Kelussia odoratissima is sedative (54), which may be due to its bioactive phthalides (55). Shojaei Asadiyeh et al in 2011 showed that major ingredients of the aerial parts of Kelussia odoratissima are Z-ligustilide and 3-N-butylphthalide (50).…”
Section: Introductionmentioning
confidence: 99%